2022
DOI: 10.3390/jpm12101601
|View full text |Cite
|
Sign up to set email alerts
|

Status of ALS Treatment, Insights into Therapeutic Challenges and Dilemmas

Abstract: Amyotrophic lateral sclerosis (ALS) is an extremely heterogeneous disease of motor neurons that eventually leads to death. Despite impressive advances in understanding the genetic, molecular, and pathological mechanisms of the disease, the only drug approved to date by both the FDA and EMA is riluzole, with a modest effect on survival. In this opinion view paper, we will discuss how to address some challenges for drug development in ALS at the conceptual, technological, and methodological levels. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 126 publications
0
11
0
Order By: Relevance
“…[46] Third, RZ facilitates glutamate reuptake by increasing the activity of glutamate transporters (EAAT receptors) expressed on astrocytes, modulating glutamate clearance from the synaptic cleft. [47] RZ is the only drug approved by both the FDA and EMA to slow down the progression of ALS [48] and provide modest survival by slowing down the progression of disease by 2-3 months. [49] However, RZ has several limitations, such as variable pharmacokinetic metabolism following oral dosing in humans not observed in animal models.…”
Section: Multi-target Ligand Approach: Riluzole-rasagiline Hybridsmentioning
confidence: 99%
See 1 more Smart Citation
“…[46] Third, RZ facilitates glutamate reuptake by increasing the activity of glutamate transporters (EAAT receptors) expressed on astrocytes, modulating glutamate clearance from the synaptic cleft. [47] RZ is the only drug approved by both the FDA and EMA to slow down the progression of ALS [48] and provide modest survival by slowing down the progression of disease by 2-3 months. [49] However, RZ has several limitations, such as variable pharmacokinetic metabolism following oral dosing in humans not observed in animal models.…”
Section: Multi-target Ligand Approach: Riluzole-rasagiline Hybridsmentioning
confidence: 99%
“…RZ is the only drug approved by both the FDA and EMA to slow down the progression of ALS [48] and provide modest survival by slowing down the progression of disease by 2–3 months [49] . However, RZ has several limitations, such as variable pharmacokinetic metabolism following oral dosing in humans not observed in animal models.…”
Section: Multi–target Ligand Approach: Riluzole–rasagiline Hybridsmentioning
confidence: 99%
“…Bryan then did the difficult work to find the precise mutation on the genome that was producing the signal: an expansion of the C9ORF72 gene consisting of a repeated six-nucleotide-long sequence [59] [10.1016/S1474-4422(10)70184-8]. Later, it was found that this mutation accounts for about 30% of inherited cases of ALS, and treatments based on this finding are now in clinical trials [46].…”
Section: Applications: Fun With Uncertainty Decision Making and Graph...mentioning
confidence: 99%
“…Despite its ability to slow the progression of ALS, its effectiveness is limited. Another drug, edaravone, has also been approved by the FDA for oral use ( 9 ) and possesses potent antioxidant properties that mitigate the effects of oxidative stress by eliminating oxidized lipids and hydroxyl radicals, which may be a key factor in the pathogenesis and development of ALS. However, clinical studies have also suggested that edaravone may be ineffective in treating ALS ( 10 ).…”
Section: Introductionmentioning
confidence: 99%